Contemporary procedural trends of Watchman percutaneous left atrial appendage occlusion in the United States: insight from the National Inpatient Sample. (25th November 2020) - Munir, M.B; Khan, M.Z; Han, F.T; Reeves, R; Hsu, J.C
Abstract: Background/Introduction: Left atrial appendage occlusion with the Watchman device has emerged as a viable therapy for stroke risk mitigation in atrial fibrillation (AF) patients. Purpose: To determine trends in real-world utilization and in-hospital adverse events from Watchman implantation since its approval by the Food and Drug Administration (FDA) in 2015. Methods: This was a retrospective cohort study utilizing data from National Inpatient Sample for calendar years 2015–2017. Watchman procedures were identified using ICD-9-CM and ICD-10-CM codes of 37.90 and 02L73DK, respectively. The outcomes assessed were associated complications and in-hospital mortality. Trends analysis were performed using analysis of variance. Results: A total of 17, 700 patients underwent Watchman implantation during the study period. There was a significantly increased trend in the number of Watchman procedures performed over the study years (from 1, 195 in 2015 to 11, 165 devices in 2017, p<0.01). A significant decline in the rate of complications (from 26.4% in 2015 to 7.9% in 2017, p<0.01) and inpatient mortality (from 1.3% in 2015 to 0.1% in 2017, p<0.01) were noted. Conclusion: Since its introduction, the Watchman procedure appears to be increasingly more common and safe in the management of stroke risk in patients with AF. Funding Acknowledgement: Type of funding source: None